Megahijub.id Online Store Marketing Strategy To Increase Consumer Purchases - Mira, Miranda; Zulistiani, Zulistiani (Universitas Nusantara PGRI Kediri, 2025)
Research aim : This study aims to analyze the marketing strategies implemented by the online store Shop Megahijub.id in an effort to increase consumer purchases. Design/Methode/Approach : Using a qualitative approach, I obtained information and data after conducting in-depth interviews with three informants based on the criteria of relevance, recommendation, and readiness. Data analysis was conducted through a process of data reduction, data presentation, and conclusion. Research Finding : The results of this study are that the Megahijub.id online shop implements a 4P marketing mix strategy, including products that focus on the quality, creativity, and uniqueness of handmade products to increase customer satisfaction and loyalty, and expand the market.Prices are set to be affordable based on production costs, quality, and comparison with competitors. Shopee is utilized as a platform to reach consumers widely, support online shopping trends, and attract purchase interest with attractive promos. Promotions are carried out through Shopee features, such as discounts, free shipping, live streaming, and affiliates to increase interaction, attract consumers, and build trust Researchers provide several suggestions that are expected to be material for evaluation and consideration. The Megahijub.id online store must continue to maintain and improve the quality of its products to ensure customer satisfaction, so that they do not switch to competing products. Theoretical contribution/Originality : This research is expected to be able to add information in the field of marketing strategy, and additional insights into the marketing field in increasing consumer purchases and competitiveness. Practitionel/Policy implication : For Megahijub.id online shop owners, researchers are expected to provide input in the form of suggestions and information to business actors regarding marketing strategies to increase sales that are being carried out by the business. For readers, this research is expected to be a reference to find out strategies to increase consumer purchases. Research limitation : In this study, there were limited informants, resulting in a lack of detailed information and data, because Megahijub.id business actors did not keep books regularly